Advantages of laparoscopic surgery in gastric gastrointestinal stromal tumors (GIST) compared to open resections - Etur dos Santos, Aline Gabriele (2024)
The aim of the study is to compare laparoscopic surgery (LAP) versus open resection (AR) for the treatment of Gastric Gastrointestinal Stromal Tumors (GIST) and to assess whether LAP has greater advantage, safety and feasibility when compared to RA. A search was carried out in the PubMed, Embase and Virtual Health Library databases using the terms: "Gastrointestinal stromal tumor", "Laparoscopy" and "Resection", and the Boolean "AND", and 9 articles were selected. LAP had lower complications, postoperative times, intraoperative blood loss, mortality and morbidity rates, and greater safety and efficacy. The best surgical technique depends on the size, location and nature of the tumor. LAP is associated with better safety and efficacy in gastric GIST surgeries. It was observed that LAP had several advantages over AR, which improved patient recovery.